Implementasi Kombinasi Hill Cipher Dan Steganografi Least Signifiaction Bit Untuk Evaluasi Kualitas Citra Digital - Putra, Redo Osi; Jumadi, Juju; Fhiter. W, Ockhy Jey (Jurnal Media Infotama, 2026)
This study implements a combination of Hill Cipher and Least Significant Bit (LSB) steganography to improve data security and evaluate digital image quality. The Hill Cipher is used to encrypt text with 2×2 key matrix, while LSB inserts the encrypted message into the least significant bits of BMP image. The research method used is applied research with stages of analysis, design, implementation, and testing. The test results show that the integration of these two methods maintains image quality with a low Mean Square Error (MSE) value (0.0001–2.9424) and high Peak Signal-to-Noise Ratio (PSNR) (83.6554–103.4438 dB), indicating visually undetectable changes. The simulations prove the effectiveness of the system in securing data without significant image degradation. The conclusion of this study is that the combination of Hill Cipher and LSB steganography is effective in securing data without significantly compromising image quality. This study also provides an alternative solution for data security by utilizing hybrid cryptography and steganography techniques.